Political Skill for Sport Professionals: Theory, Research, and Career Success Implications - G. Matthew Robinson; Marshall J Magnusen; Glenn Miller (Journal of Applied Sports Management, 2020)
Motivated by an increasing interpersonal aspect to the profession of sport coaching, the importance of being socially effective as a coach has multiplied in significance. This review specifically considers the social effectiveness construct, political skill, as a crucial aspect to career success through the perspective of a sport coaching lens. Political skill refers to the ability to effectually understand others at work, and to then use that information to influence others to behave in ways that enhance one’s personal and/or organizational objective. Political skill is a means through which sport coaches may be able to build and maintain important and influential relationships with key stakeholders (e.g., athletic directors), thus improving the possibility of a successful coaching career. This article presents a review of theoretical foundations for the association between political skill and career success as well as practical applications (e.g., active listening, empowerment, volunteerism) for sport coaches when managing important stakeholder relationships. Research suggestions for the continued advancement of political skill research are also provided.
Keywords: Coaching; Influence; Management; Organizational Behavior; Social Exchange